Statistics and IQ in Developing Countries: A Note - Oasis Kodila-Tedika; Simplice A. Asongu; Florentin Azia-Dimbu (African Governance and Development Institute (AGDI), 2015)
The purpose of this study is to assess the nexus between intelligence (or human capital) and statistical capacity in developing countries. The line of inquiry is motivated essentially by: (i) the scarce literature devoted to elucidating poor statistics in developing countries and (ii) an evolving stream of literature on knowledge economy. We have established a positive association between intelligence quotient (IQ) and statistical capacity. The relationship is: (i) consistent with the employment of alternative specifications based on varying conditioning information sets and (ii) robust to the control of outliers. Policy implications are discussed.
Keywords: D02; D73; I20; 330; Statistics; Intelligence; Developing countries